MCPHERSON, J. Inventory of documents - MCPHERSON, J. (ARCA, 2018)
Letter from Genl. Hertzog to Mr AK McPherson; three newspaper clippings
COVERAGE: 1938-1966; 0.02 metre
Keywords: MCPHERSON, J.; Inventories; Politicians; National Party